2019
DOI: 10.3390/math7090813
|View full text |Cite
|
Sign up to set email alerts
|

New Analytical Solutions for Time-Fractional Kolmogorov-Petrovsky-Piskunov Equation with Variety of Initial Boundary Conditions

Abstract: The generalized time fractional Kolmogorov-Petrovsky-Piskunov equation (FKPP),, which plays an important role in engineering, chemical reaction problem is proposed by Caputo fractional order derivative sense. In this paper, we develop a framework wavelet, including shift Chebyshev polynomial of the first kind as a mother wavelet, and also construct some operational matrices that represent Caputo fractional derivative to obtain analytical solutions for FKPP equation with three different types of Initial Boundar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…On contrast with the solutions of the KPP model in Refs. [ [33] , [34] , [35] , [36] , [37] , [38] , [39] ], we observed that all of the authors used to find exact traveling wave solutions by the relation . But our solution covers all of their solutions when we consider both are linear in the transformation relation .…”
Section: Comparison and Limitationsmentioning
confidence: 96%
See 2 more Smart Citations
“…On contrast with the solutions of the KPP model in Refs. [ [33] , [34] , [35] , [36] , [37] , [38] , [39] ], we observed that all of the authors used to find exact traveling wave solutions by the relation . But our solution covers all of their solutions when we consider both are linear in the transformation relation .…”
Section: Comparison and Limitationsmentioning
confidence: 96%
“…12 ). Besides this, we can use fractional power of the time variable in the function taking constant which cover the fractional solutions obtained by the solutions of [ 33 , 38 ]. Actually, arbitrariness of time varying function suggested appreciating machinery for chaotic behaviors in ocean engineering phenomena in identifiable complications.…”
Section: Comparison and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation